THE INFLUENCE OF WORK MOTIVATION AND EMPLOYEE COMPETENCE ON CUSTOMER SATISFACTION AT THE WANASARI COMMUNITY HEALTH CENTER REGIONAL TECHNICAL IMPLEMENTATION UNIT (UPTD) - Yulin Puspitasari; Adriza; Nurwulan Kusumadevi (STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the influence of work motivation and employee competence on customer satisfaction at the Wanasari Community Health Center (Puskesmas) Regional Technical Implementation Unit (UPTD). The research is grounded in the importance of motivation and competence for customer satisfaction at this facility. A quantitative approach was employed, combining descriptive and verificative methods. Data were collected through questionnaires administered to 52 customers of the Wanasari Puskesmas UPTD and analyzed using multiple linear regression. The results indicate that both motivation and competence have a positive and significant effect on customer satisfaction, both partially and simultaneously. The study concludes that motivation and competence are essential for optimizing customer satisfaction at the Wanasari Puskesmas UPTD.